The effect of breast size and bra type on comfort for UK female police officers wearing body armour - Malbon, Christopher; Knock, Clare; Critchley, Richard; Carr, Debra J. (Elsevier, 2019)
Within the Police service of England and Wales the wearing of ballistic and stab resistant body armour is common, with most police forces mandating its usage when away from the police station. Of all the serving police officers in England and Wales 29.1% are female (Hargreaves et al., 2017). A survey was developed and then distributed by the Police Federation of England and Wales to all servicing police officers up to the rank of Inspector. The survey returned 2633 responses after cleaning of the data. From the responses it was seen that the predominant bra type worn is underwired (71%) and the predominant UK bra size is 34B (9%). It was also determined that the predominant areas where the body armour either rubbed or caused discomfort were the left and right anterior mammary regions and the posterior lateral sacral region. By understanding the distribution of bra size, type of bra worn and areas of discomfort or rubbing it helps further understand the issues faced by female police officers and how body armour design could be improved.
Keywords: UK bra size; Sports bra; Underwired bra; Activity